Global, regional, and national burden of liver cancer attributable to high BMI, 1990-2021, with future projections to 2040 - Ma, Teng; Lu, Yawen; Liu, Kaiyan; Liu, Na; Liu, Qian; Ding, Ziyuan; Ma, Jianfeng; Wang, Yongfeng; Li, Sheng (Frontiers in Oncology, 2026)
BackgroundHigh body mass index (BMI) is a key metabolic risk for liver cancer, yet global assessments of its impact are limited. This study analyzes the liver cancer burden linked to high BMI from 1990 to 2021, using frontier analysis to evaluate prevention efficiency at different SDI levels and providing future predictions of the global burden up to 2040 to guide public health strategies.MethodWe analyzed global burden mortality and disability rates using 2021 data, applying age-period-cohort modeling to assess the temporal dynamics of BMI-related liver cancer burden, adjusting for period and cohort effects across 204 countries and 21 regions, stratified by sex, age, and Sociodemographic Index (SDI). The analysis incorporated frontier efficiency estimates to understand the best achievable burden reduction at each SDI level and utilized a Bayesian framework for future trend predictions.ResultFrom 1990 to 2021, high BMI-related liver cancer deaths reached 46,200.88 worldwide, predominantly affecting men, especially ages 70–74 and 60–64 for DALYs. The disease burden varies nonlinearly with SDI, with regional disparities: Southeastern South America and Central/Eastern Europe face the highest impact, despite higher SDIs in Japan, South Korea, and Singapore, where the burden is comparatively lower. Frontier analysis reveals that countries with higher SDI levels have optimized prevention and control strategies, achieving lower burdens, while lower SDI regions still face significant challenges. The future projections indicate that the global burden of high BMI-related liver cancer will continue to rise by 2040, with rapid increases in male populations, although female predictions show more gradual growth.ConclusionHigh BMI contributes to the increasing and unequal global burden of liver cancer, mainly impacting men, seniors, and middle-to-high SDI areas. Urgent, targeted efforts are needed to combat obesity, metabolic issues, and healthcare inequalities to reduce future risks. Future prevention strategies should incorporate continuous monitoring and adaptive responses to dynamic factors influencing liver cancer attributable to high BMI.